Pupa of Elasmocylidrus Tricolor Corporaal - Mathur, R. N. (Indian Forester, 1959)
Elasmocylidrus tricolar Corp. (Cleridae) is predaceous on several kinds of borers, particularly Bostrychidae. Its hosts, distributional records and the characters of pupa are included.